A Case Study on the Impact of an Adapted Community Jury in Shaping the Nutrition Standards for Hospital Menus in New South Wales Australia - Tara Dimopoulos-Bick; Melanie Schier; Kim Crawley; Kim Sutherland (Patient Experience Journal)
Community juries are a form of deliberative democracy and can engage community groups in decision-making about healthcare and service delivery issues and priorities. They can provide insights and value-based perspectives from community groups and are particularly important in resolving perennial and complex system challenges. One such challenge is nutrition in hospitals–where there is a need to balance nutrition support, variety, taste and cost. The New South Wales (NSW) public health system in Australia operates more than 200 public hospitals. When revising the Nutrition Standards in 2021, stakeholders debated the upper limits of sodium (salt) and saturated fat in food products on hospital menus. Our case study describes how a jury of 12 community members received expert-informed information and deliberated on various evidence sources to reach a verdict, recommending that there should be upper limits on sodium (salt) and saturated fat in food products on hospital menus. It offers practical suggestions on adapting a community jury approach to strengthen patient, family, and community engagement across healthcare systems.